Experimental and Numerical Study of Discharge Capacity and Sediment Profile Upstream of Piano Key Weirs with Different Plan Geometries - Abhash A.; Pandey K.K. (My University, 2025)
Piano key weirs (PKWs) are an improved form of labyrinth weirs, which are becoming popular as a more hydraulically efficient and cost-effective type of weir over its counterparts for both spillway and river flow conditions. More than thirty PKWs are already in construction worldwide, with constructions in India at Swara Kuddu. More than twenty parameters influence the flow over a PKW, and as such, the flow hydraulics near PKW is complex. It is imperative to study the performance of different shapes of PKW to know which shape offers more hydraulically and cost-effective advantages over other shapes. The present study combines the experimental and numerical study of discharge capacity and sediment carrying capacity of the different plan geometries of PKW. The experimental study of the discharging capacity of PKW has been carried out at eighteen discharge points for three plan geometries of PKW. A numerical study using ANSYS FLUENT has also been carried out at five discharges and compared with the experimental results. Vertical velocity near a weir is an essential factor facilitating the uplift of sediment. Sediment profile in the channel has been studied at three discharges experimentally for two types of PKWs: RPKW and TPKW6, all for free-flow conditions. The numerical study has also been carried out at these experimental discharges for studying the vertical component of velocity (v) upstream of PKW. An attempt has been made to isolate critical areas where the sediments are being lifted by the turbulence mechanism, thus helping them pass over the weir. The study shows PKW with a rectangular plan (RPKW) to be more hydraulically efficient than TPKWs with six-degree and thirteen-degree lateral crest variations (TPKW6 & TPKW13). The study also shows RPKW to be more self-cleaning in nature than its trapezoidal counterpart (TPKW6). Numerical study shows a close resemblance to the experimental results with errors well within permissible limits implying its greater use in ascertaining complex flows around hydraulic structures. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.